2021
DOI: 10.3390/recycling6010002
|View full text |Cite
|
Sign up to set email alerts
|

An Additive Model to Predict the Rheological and Mechanical Properties of Polypropylene Blends Made by Virgin and Reprocessed Components

Abstract: In this work, an additive model for the prediction of the rheological and mechanical properties of monopolymer blends made by virgin and reprocessed components is proposed. A polypropylene sample has been reprocessed more times in an extruder and monopolymer blends have been prepared by simulating an industrial process. The scraps are exposed to regrinding and are melt reprocessed before mixing with the virgin polymer. The reprocessed polymer is, then, subjected to some thermomechanical degradation. Rheologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…and, then, the reduction of the Newtonian viscosity means a reduction of the molecular weight, which can be calculated using Equation (3) [22] as follows:…”
Section: Resultsmentioning
confidence: 99%
“…and, then, the reduction of the Newtonian viscosity means a reduction of the molecular weight, which can be calculated using Equation (3) [22] as follows:…”
Section: Resultsmentioning
confidence: 99%
“…The Newtonian viscosity is a strong function of the molecular weight (see Equ ( 5)) [17]: 3.4 and then, the molecular weight of the sample photo-oxidized can be calculated Equation ( 6 As reported before, the decrease of the molecular weight enhances the crystalliz rate and the crystallinity degree. In Figure 3 the thermograms of the same sample reported.…”
Section: Characterization Of Photo-oxidized Ppmentioning
confidence: 96%
“…It has been already shown that if P(M i ) is the value of the generic property of a mono-polymer blend having recycled fractions until the i-th photo-oxidized polymer, [17]:…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of waste plastic is a vital issue that must be addressed on a global scale through policy and proper waste management. After some careful research [19][20][21][22], the blending of raw and reprocessed PP has become routine and the process usually involves adding 10% to 30% recycled material to raw components to avoid any serious changes in the mechanical properties or process ability of the product. These reprocessed PP blends have the same properties and are very similar to virgin PP; the only clear change is a decrease in the molecular weight caused by the repetitive melt processing operations.…”
Section: Introductionmentioning
confidence: 99%